Mechanical determinants of the U-shaped speed-energy cost of running relationship - Carrard, A.; Fontana, E.; Malatesta, D. (Frontiers in Physiology, 2018)
Purpose: The aim of this study was to investigate the relationship between the energy cost of running (Cr) and speed and its mechanical determinants by comparing running in normal [100% body weight (BW)] and reduced (20% and 60% BW) gravity conditions at several speeds (2.25, 3.17, 4.08, and 5.00 m·s-1) in experienced runners.